Cigarette smoking and depression comorbidity: systematic review and proposed theoretical model. (26th October 2016) - Mathew, Amanda R.; Hogarth, Lee; Leventhal, Adam M.; Cook, Jessica W.; Hitsman, Brian
Abstract: Background and Aims: Despite decades of research on co‐occurring smoking and depression, cessation rates remain consistently lower for depressed smokers than for smokers in the general population, highlighting the need for theory‐driven models of smoking and depression. This paper provides a systematic review with a particular focus upon psychological states that disproportionately motivate smoking in depression, and frame an incentive learning theory account of smoking‐depression co‐occurrence. Methods: We searched PubMed, Scopus, PsychINFO and CINAHL to December 2014, which yielded 852 papers. Using pre‐established eligibility criteria, we identified papers focused on clinical issues and motivational mechanisms underlying smoking in established, adult smokers (i.e. maintenance, quit attempts and cessation/relapse) with elevated symptoms of depression. Two reviewers determined independently whether papers met review criteria. We included 297 papers in qualitative synthesis. Results: Our review identified three primary mechanisms that underlie persistent smoking among depressed smokers: low positive affect, high negative affect and cognitive impairment. We propose a novel application of incentive learning theory which posits that depressed smokers experience greater increases in the expected value of smoking in the face of these three motivational states, which promotes goal‐directed choice of smoking behavior over alternative actions. Conclusions: The incentive learning theory accounts for current evidence on how depression primes smoking behavior and provides a unique framework for conceptualizing psychological mechanisms of smoking maintenance among depressed smokers. Treatment should focus upon correcting adverse internal states and beliefs about the high value of smoking in those states to improve cessation outcomes for depressed smokers.